Scientific writing: A way to improve students' information literacy and reasoning ability - Tutut Indria Permana; Diani Fatmawati; Moh. Mirza Nuryady; Ikmal Reza Fahlevy; Ivan Ardiansyah (Journal of Community Service and Empowerment, 2023)
The abilities students need to fulfill the SDGs are current information literacy and reasoning skills. Apart from going through the learning process, this ability can be developed by the participation of students in extracurricular activities related to scientific writing. This service activity aims to provide scientific writing assistance for students at Batu Islam High School to improve information literacy and reasoning skills. The form of training carried out is to provide material related to various research that can be carried out by students both inside and outside the classroom and provide assistance to take part in scientific writing competitions at the national level. The instruments for community service activities used are information literacy questions and observation sheets. Data analysis was carried out descriptively. The results of community service activities show that there is an increase in students' information literacy and reasoning abilities. The results of the participation of students in the national competition won the third prize